Analysis of multi-year near-surface ozone observations at the WMO/GAW "Concordia" station (75°06′S, 123°20′E, 3280 m a.s.l. – Antarctica). (March 2018) - Cristofanelli, Paolo; Putero, Davide; Bonasoni, Paolo; Busetto, Maurizio; Calzolari, Francescopiero; Camporeale, Giuseppe; Grigioni, Paolo; Lupi, Angelo; Petkov, Boyan; Traversi, Rita; Udisti, Roberto; Vitale, Vito
Abstract: This work focuses on the near-surface O3 variability over the eastern Antarctic Plateau. In particular, eight years (2006–2013) of continuous observations at the WMO/GAW contributing station "Concordia" (Dome C–DMC: 75°06′S, 123°20′E, 3280 m) are presented, in the framework of the Italian Antarctic Research Programme (PNRA). First, the characterization of seasonal and diurnal O3 variability at DMC is provided. Then, for the period of highest data coverage (2008–2013), we investigated the role of specific atmospheric processes in affecting near-surface summer O3 variability, when O3 enhancement events (OEEs) are systematically observed at DMC (average monthly frequency peaking up to 60% in December). As deduced by a statistical selection methodology, these OEEs are affected by a significant interannual variability, both in their average O3 values and in their frequency. To explain part of this variability, we analyzed OEEs as a function of specific atmospheric variables and processes: (i) total column of O3 (TCO) and UV-A irradiance, (ii) long-range transport of air masses over the Antarctic Plateau (by Lagrangian back-trajectory analysis – LAGRANTO), (iii) occurrence of "deep" stratospheric intrusion events (by using the Lagrangian tool STLEFLUX). The overall near-surface O3 variability at DMC is controlled by a day-to-day pattern, which strongly points towards a dominating influence of processes occurring at "synoptic" scales rather than "local" processes. Even if previous studies suggested an inverse relationship between OEEs and TCO, we found a slight tendency for the annual frequency of OEEs to be higher when TCO values are higher over DMC. The annual occurrence of OEEs at DMC seems related to the total time spent by air masses over the Antarctic plateau before their arrival to DMC, suggesting the accumulation of photochemically-produced O3 during the transport, rather than a more efficient local production. Moreover, the identification of recent (i.e., 4-day old) stratospheric intrusion events by STEFLUX suggested only a minor influence (up to 3% of the period, in November) of "deep" events on the variability of near-surface summer O3 at DMC. Highlights: Near-surface O3 was observed at Concordia (Antarctica) from 2006 to 2013. O3 enhancement events (OEE) were systematically observed from November to February. OEE occurrence related to the total time spent by air masses over the plateau. The near-surface O3 is controlled by "synoptic-scale" rather than "local" processes.